Exposure to parasitic infections determines features and phenotypes of active convulsive epilepsy in Africa - Langat, NK; Kariuki, SM; Kamuyu, G; Kakooza-Mwesige, A; Owusu-Agyei, S; Ae-Ngibise, K; Wang'ombe, A; Ngugi, AK; Masaja, H; Wagner, RG; Newton, CRJC (F1000Research, 2021)
Background: Epilepsy affects 70 million people worldwide, 80% of whom are in low-and-middle income countries (LMICs). Infections of the central nervous system (CNS) contribute considerably to the burden of epilepsy in LMICs, but the nature and presentation of epilepsy following these infections is not fully understood. We examined if epilepsy foutcomes are associated with the exposure to parasitic infections. Methods: This was a case-comparison study nested in a cross-sectional survey of people with active convulsive epilepsy, with cases as those exposed to parasitic infections, and comparison as those unexposed. Associations of exposure to parasites with clinical and electroencephalographic features of epilepsy were done using a modified mixed effects Poisson regression model across five sites in Africa. Multiplicative and additive scale (RERI) interactions were explored to determine the effect of co-infections on epilepsy features. Population attributable fractions (PAF) were calculated to determine the proportion of severe clinical and electroencephalographic features of epilepsy attributable to CNS infections. Results: A total of 997 participants with active convulsive epilepsy from the five African sites were analyzed, 51% of whom were males. Exposure to parasitic infections was associated with more frequent seizures in adult epilepsy (relative risk (RR)=2.58, 95% confidence interval (95%CI):1.71-3.89). In children, exposure to any parasite was associated with convulsive status epilepticus (RR=4.68, (95%CI: 3.79-5.78), intellectual disabilities (RR=2.13, 95%CI: 1.35-3.34) and neurological deficits (RR=1.92, 95%CI: 1.42-2.61). Toxoplasma gondii and Onchocerca volvulus interacted synergistically to increase the risk of status epilepticus (RERI=0.91, 95%CI=0.48-1.35) in the data pooled across the sites. Exposure to parasitic infections contributed to 30% of severe features of epilepsy as shown by PAF. Conclusions: Parasitic infections may determine features and phenotypes of epilepsy through synergistic or antagonistic interactions, which can be different in children and adults. Interventions to control or manage infections may reduce complications and improve prognosis in epilepsy.